Experiments on groundnut seed storage - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
In Senegal and the Gambia high post-harvest losses are incurred because of the groundnut seed beetle caryedon serratus which infects groundnuts while they are drying off in the field. The On-Farm Seed Project (OFSP) and the Peace Corps AFSI Project...